2017
DOI: 10.1590/1678-4685-gmb-2016-0284
|View full text |Cite
|
Sign up to set email alerts
|

Description of the karyotypes of Stejneger's beaked whale (Mesoplodon stejnegeri) and Hubbs’ beaked whale (M. carlhubbsi)

Abstract: The genus Mesoplodon (Cetacea: Odontoceti: Ziphiidae) is one of the few cetacean genera with the karyotype 2n = 42. The 2n = 42 karyotype of M. europaeus and M. carlhubbsi is largely consistent with the general cetacean karyotype 2n = 44, although other 2n = 42 karyotypes do not exhibit clear homologies with the general cetacean karyotype. Therefore, the chromosomes of Mesoplodon species may be the key to understanding cetacean karyological evolution. In the present study, the male karyotypes of M. stejnegeri … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
(24 reference statements)
1
5
0
Order By: Relevance
“…Based on these HSBs, we reconstructed the ancestral chromosomes for Cetruminantia (28), Bovidae (30), and Odontoceti (22) ( Tables S8–S10 ). This analysis confirmed that the number of ancestral chromosomes of Odontoceti is the same as that of most extant cetacean families (22 chromosome pairs) and different from that of superfamily Physeteroidea ( ÁRnason, 1974 ) and family Ziphiidae ( Kurihara et al., 2017 ) (21 chromosome pairs). Thus, we propose a model of chromosome evolution in cetaceans in which a chromosome fusion event likely occurred in the physeterids (i.e., sperm whales).…”
Section: Resultssupporting
confidence: 68%
“…Based on these HSBs, we reconstructed the ancestral chromosomes for Cetruminantia (28), Bovidae (30), and Odontoceti (22) ( Tables S8–S10 ). This analysis confirmed that the number of ancestral chromosomes of Odontoceti is the same as that of most extant cetacean families (22 chromosome pairs) and different from that of superfamily Physeteroidea ( ÁRnason, 1974 ) and family Ziphiidae ( Kurihara et al., 2017 ) (21 chromosome pairs). Thus, we propose a model of chromosome evolution in cetaceans in which a chromosome fusion event likely occurred in the physeterids (i.e., sperm whales).…”
Section: Resultssupporting
confidence: 68%
“…Most studies on cell cultures of wild cetaceans have thus targeted fibroblasts. In previous studies, cetacean fibroblast cells have been isolated from skin, , lungs, testes, muscle, and cartilage . This study proposed a non-invasive and efficient cell culture method using the flipper tip of a stranded cetacean.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, cetacean fibroblast cells have been isolated from skin, 26,33−41 lungs, 38 testes, 38 muscle, 42 and cartilage. 42 This study proposed a non-invasive and efficient cell culture method using the flipper tip of a stranded cetacean. Although elapsed time after death (including the time spent for sampling) is a critical issue for cell culture, the tissue samples can be easily collected from the edge of the flipper.…”
Section: Resultsmentioning
confidence: 99%
“…M. carlhubbsi in the study of Arnason et al [1977] were female. In the paper by Kurihara et al [2017], the Y chromosomes of M. stejnegeri and M. carlhubbsi appear to be small and metacentric. In the current individual of M. densirostris, the Y is significantly larger.…”
Section: Discussionmentioning
confidence: 92%
“…There are currently 22 recognised species of beaked whales. Fifteen of these are contained within the genus Mesoplodon, and only 3 of these species have been karyotyped: Mesoplodon europaeus [Arnason et al, 1977], M. carlhubbsi [Arnason et al, 1977;Kurihara et al, 2017], and M. stejnegeri [Kurihara et al, 2017]. These 3 species have an X chromosome with a large distal heterochromatic block on the long arm and also have 42 chromo-somes, whereas most cetaceans have 44 [Arnason et al, 1977].…”
Section: Introductionmentioning
confidence: 99%